Mediating role of emotion regulation difficulty on the relationship between maladaptive schemas and depression symptoms - Zahra Khani; Mohammad Ali Besharat; Hojjatollah Farahani (مجله علوم روانشناختی, 2020)
Background: Symptoms of depression decrease the quality of life and make people susceptible to depressive disorders. But the main question of the present study is whether the difficulty of emotion regulation plays a mediating role in this regard? Aims: To determine the mediating role of emotion regulation difficulty in the relationship between early maladaptive psychosis and depressive symptoms. Method: This study was a correlational study. For this purpose, 300 students (158 females, 142 males) were selected through convenience sampling from Tehran University students. The instruments were: Young's Psychosis Questionnaire (Young, 1998), Depression Scale, Anxiety, Stress (Lovebound & Lovebird, 1995) and Emotion Regulation Difficulty Scale (Gertz & Romer, 2004). Path analysis was used to analyze the data. Results: There was a significant positive relationship between early maladaptive psychosis, emotion regulation difficulty, and depressive symptoms (p<0/01). There were early maladaptations and symptoms of depression (p<0/05). Conclusions: Early maladaptive psychosis affects the symptoms of depression through the difficulty of emotion regulation. Therefore, in order to prevent the development of depressive symptoms, in addition to reducing the negative features of early maladaptive psychoses, it is necessary to provide backgrounds for the regeneration of emotional regulation processes in order to increase mental health